2005
DOI: 10.1097/01.ta.0000188130.99626.8c
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Washers in Cannulated Screw Fixation of Femoral Neck Fractures

Abstract: This study confirms previous findings in the literature that increased age, a displaced fracture type, and poor reduction increase the risk of fixation failure. Contradictory to current belief, there was no significant association between the distance of the inferior screw to the inferior/medial femoral neck cortex and fixation failure. A novel finding of the present study is that the use of washers significantly decreases the risk of fixation failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Reduction quality was measured according to the Garden classification and was classified as anatomic, acceptable (within the range of 155 to 180 degrees in both anteroposterior and lateral radiographs), borderline to unacceptable (<155 or >180 degrees in either view) [23]. Loss of fracture reduction was defined as greater than 208 change in angulation and/or greater than 5 mm translation in AP or lateral views [24]. Nonunion was defined as persistent fracture gap at least one year postoperatively.…”
Section: Patientsmentioning
confidence: 99%
“…Reduction quality was measured according to the Garden classification and was classified as anatomic, acceptable (within the range of 155 to 180 degrees in both anteroposterior and lateral radiographs), borderline to unacceptable (<155 or >180 degrees in either view) [23]. Loss of fracture reduction was defined as greater than 208 change in angulation and/or greater than 5 mm translation in AP or lateral views [24]. Nonunion was defined as persistent fracture gap at least one year postoperatively.…”
Section: Patientsmentioning
confidence: 99%
“…This effect was even greater in a logistic regression multivariate analysis with an 11.2 times higher odds ratio for failure without washers. 11 This finding was somewhat surprising, as washers do not provide any resistance to varus collapse and do not prevent screws from backing out.…”
Section: Discussionmentioning
confidence: 86%
“…11 In that study, fixation failure was defined as a composite outcome including loss of fracture reduction (.20 degrees change in angulation and/or .5 mm translation in anteroposterior or lateral views), implant cutout, or implant breakage. 11 With washers in a univariate analysis, failure was reduced by 71%. This effect was even greater in a logistic regression multivariate analysis with an 11.2 times higher odds ratio for failure without washers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one prospective multicenter study, no difference was found in revision to arthroplasty rates in osteoporotic and osteopenic patients treated with a variety of fixation methods [51]. In another, older age was one of several factors influencing variability in fixation failure, suggesting a possible role of bone quality [147]. In summary, although age, bone quality, and type of fixation device used may relate to the strength of fixation and healing potential in femoral neck fractures, the relative importance of each of those factors has not been clearly demonstrated.…”
Section: Fracture Fixation and Repairmentioning
confidence: 98%